Population pharmacokinetics of unbound and total dolutegravir concentrations in children aged 12 years and older: a PK substudy of the SMILE trial. (3rd March 2023) - Abdalla, Seef; Compagnucci, Alexandra; Zheng, Yi; Tréluyer, Jean-Marc; Saidi, Yacine; Ramos, José T; Coelho, Alexandra; Riault, Yoann; Cressey, Tim R; Hirt, Déborah; ,
Abstract: Background: SMILE, a multicentre randomized trial, compared the efficacy and safety of switching virologically suppressed children and adolescents with HIV to a once-daily dual regimen of dolutegravir plus ritonavir-boosted darunavir versus continuing standard ART. Within a nested pharmacokinetic (PK) substudy, we performed a population PK analysis to describe total and unbound dolutegravir plasma concentrations in children and adolescents receiving this dual therapy. Methods: Sparse blood samples were obtained during follow-up for dolutegravir quantification. A population PK model was developed to simultaneously describe total and unbound dolutegravir concentrations. Simulations were performed and were compared with the protein-adjusted 90% inhibitory concentration (IC90 ) and the in vitro IC50, respectively. Dolutegravir exposures in children aged ≥12 years were also compared with values in treatment-experienced adults. Results: Four hundred and fifty-five samples from 153 participants aged between 12 and 18 years were collected for this PK analysis. A one-compartment model with first-order absorption and elimination best described unbound dolutegravir concentrations. The relationship between unbound and total dolutegravir concentrations was best characterized by a non-linear model. Unbound dolutegravir apparent clearance was significantly influenced by total bilirubin concentrations and by Asian ethnicity. All children and adolescents had trough concentrations well above the protein-adjusted IC90 and the in vitro IC50 values. Dolutegravir concentrations and exposures were also similar to those obtained in adults receiving dolutegravir 50 mg once daily. Conclusions: A once-daily 50 mg dolutegravir dose for children and adolescents produces adequate total and unbound concentrations when used as part of dual therapy with ritonavir-boosted darunavir.